Analisis Faktor-Faktor Penyebab Rendahnya Motivasi Belajar Siswa Pada Mata Pelajaran IPS Kelas IV SD Negeri 1 Sunggutan - Heti Sanjaya; Misdalina Misdalina; Ida Suryani (Journal on Education, 2023)
The results of observations at SD Negeri 1 Sunggutan show that students have to read a lot, causing students' enthusiasm for learning. In the case of dense material needs, teachers do not learn through the media, but rather through the lecture method. This method results in students not being motivated to continuously learn. In addition, teachers lack ideas for learning even less interesting and creative, and students are less active in reading lesson materials. The purpose of this study was to determine the faktors causing the low motivation to learn students in the Social Studies Class IV subject of SD Negeri 1 Sunggutan. The informants of this study were 25 students in grade IV. The data collection used is observation, and documentation. Data analysis using data triangulation. As a result of the readiness and mastery of the teacher to prepare spaces, learning tools (package books and LKS), teachers also carry out the learning process starting with preliminary activities with class conditioning, providing motivation, appreciating, conveying indicators of competency achievement, and checking student readiness. The faktors causing the low motivation to learn social studies subjects at SD Negeri 1 Sunggutan are that students do not pay attention to the teacher's explanation, students do not concentrate when attending lessons, and students do not have confidence in following lessons. In addition, there is a lack of varied learning methods, teachers do not use learning media, and lack of learning resources